Measles outbreak investigation in Tocha district, southwestern Ethiopia: an unmatched case–control study - Simon Fikadu Tefera; Nigatu Admasu; Habtamu Abebe; Gemechu Chemeda Feyisa; Gachana Midaksa (Frontiers in Public Health, 2024)
BackgroundMeasles continues to be a public health challenge in Ethiopia. Rumors of suspected measles were notified on April 8, 2023 from Tocha district. We conducted an assessment to describe measles outbreak and determine risk factors for measles infection in the Tocha district of the Dawuro zone, Southwest Ethiopia.MethodsWe conducted a 1:2 unmatched case–control studies from April to May 2023. We took all 147 cases registered on line list for descriptive analyses. We used a total of 74 randomly selected cases and 147 controls for case–control part. Any person in Tocha district with laboratory-confirmed measles IgM antibody; or any suspected person epidemiologically linked to confirmed measles cases from March 23 to April 26 2023, were included in the case. Neighborhood who did not fulfill this standard case definition were included in controls. Data were collected using standardized questionnaires deployed on Kobo Collect. Descriptive analyses were conducted using Epi info version 7.2.5.0. The analyses were performed using Statistical Package for Social Science (SPSS) version 26. Binary logistic regression analyses were utilized to select candidate variables. We conducted multiple logistic regression analysis to identify determinants of measles infection at a p value ≤0.05 with 95% confidence interval.ResultsThe overall attack rate of 22.64/10,000 for general population and 104.59/10,000 among under-five children were attributed to the outbreak with a case fatality rate of 2.72%. Vaccine coverage in the last year and this year were 73.52 and 53.88%, respectively, while vaccine effectiveness in the district was 79%. Poor house ventilation (AOR = 3.540, 95% CI: 1.663–7.535) and having contact history with the case (AOR = 2.528, 95% CI: 1.180–4.557) were positively related to measles infection while being previously vaccinated for measles (AOR = 0.209, 95% CI: 0.180–4.577) reduce risk of measles infections.ConclusionThe highest attack rate was observed among children under 5 years of age, with a case fatality rate of 2.72%. Vaccination coverage was less than what expected to develop herd immunity. Strategies to increase vaccination coverage and strengthening surveillance systems for rumor identification and early responses to prevent person to person transmission are recommended.